2009
DOI: 10.1074/jbc.m109.051409
|View full text |Cite
|
Sign up to set email alerts
|

The Divalent Metal Transporter Homologues SMF-1/2 Mediate Dopamine Neuron Sensitivity in Caenorhabditis elegans Models of Manganism and Parkinson Disease

Abstract: Parkinson disease (PD) and manganism are characterized by motor deficits and a loss of dopamine (DA) neurons in the substantia nigra pars compacta. Epidemiological studies indicate significant correlations between manganese exposure and the propensity to develop PD. The vertebrate divalent metal transporter-1 (DMT-1) contributes to maintaining cellular Mn 2؉ homeostasis and has recently been implicated in Fe 2؉ -mediated neurodegeneration in PD. In this study we describe a novel model for manganism that incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
120
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 86 publications
(107 reference statements)
2
120
0
Order By: Relevance
“…Additionally, acute Mn exposure can lead to mitochondrial inhibition by disrupting mitochondrial membrane potential (Δψ) and oxygen consumption. Oxidative stress also resulted in the neurodegeneration of dopaminergic (DAergic) neurons, indicated by the fact that treated worms showed a significant decrease in DA concentration compared to untreated worms [143]. Similar neurodegeneration has been shown following exposure to mancozeb [144,145].…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 63%
See 2 more Smart Citations
“…Additionally, acute Mn exposure can lead to mitochondrial inhibition by disrupting mitochondrial membrane potential (Δψ) and oxygen consumption. Oxidative stress also resulted in the neurodegeneration of dopaminergic (DAergic) neurons, indicated by the fact that treated worms showed a significant decrease in DA concentration compared to untreated worms [143]. Similar neurodegeneration has been shown following exposure to mancozeb [144,145].…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 63%
“…Manganese exposure by itself has been shown to result in a variety of detrimental effects in C. elegans [146][147][148]. One study demonstrates that even short exposures (30 min) to manganese result in production of ROS, as evidenced by a drastic increase in glutathione levels [143]. In this study, worms exposed to 50 mM of MnCl2 experienced a two-fold increase in the amount of ROS production.…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 64%
See 1 more Smart Citation
“…Mn exposure in worms has been associated with morphological alterations, reduced longevity, oxidative stress, and behavioral alterations, such as decreased head trash and body-bend frequencies Benedetto et al 2010;Settivari et al 2009;Wang and Xing 2008). Particularly, DAergic degenerations were observed after acute exposure to this metal (Benedetto et al 2010;Settivari et al 2009).…”
Section: Studies In Caenorhabditis Elegansmentioning
confidence: 96%
“…Particularly, DAergic degenerations were observed after acute exposure to this metal (Benedetto et al 2010;Settivari et al 2009). Benedetto et al, making use of various genetic strains of C. elegans in conjunction with the fluorescent-tagging of different classes of neuron types, have demonstrated that Mn causes a dose-dependent and specific degeneration of DAergic neurons (Benedetto et al 2010).…”
Section: Studies In Caenorhabditis Elegansmentioning
confidence: 97%